A Z-scheme NiCo2O4/S codoped 1D g-C3N4 heterojunction for solar-light-sensitive photocatalytic degradation of antibiotics in aqueous solutions exemplified by tetracycline. Issue 1 (7th December 2021) - Nguyen, Thanh-Binh; Ho, Phung-Ngoc-Thao; Chen, Chiu-Wen; Huang, C. P.; Doong, Ruey-an; Dong, Cheng-Di
Abstract : A NiCo2 O4 nanoparticle (NP) and sulfur codoped hollow tubular g-C3 N4 (NiCo–S@CN) catalyst was synthesized by a hydrothermal pyrolysis method and used to remove pharmaceuticals, exemplified by the antibiotic tetracycline (TC), from water under solar light irradiation. Abstract : A NiCo2 O4 nanoparticle (NP) and sulfur codoped hollow tubular g-C3 N4 (NiCo–S@CN) catalyst was synthesized by a hydrothermal pyrolysis method and used to remove pharmaceuticals, exemplified by the antibiotic tetracycline (TC), from water under solar light irradiation. The synergistic effect of NiCo2 O4 NPs and S@CN nanotubes in the Z-scheme heterojunction significantly enhanced the photocatalytic reactivity of the NiCo–S@CN catalyst, under solar light, toward TC degradation. Factors such as catalyst dosage, pH, TC concentration, and temperature that controlled TC degradation in synthetic and natural water media were studied. Langmuir–Hinshelwood kinetics were observed in the photocatalytic degradation of TC over NiCo–S@CN. The photocatalytic performance was the best at the catalyst dosage of 200 mg L −1 . The initial effect of pH on TC photodegradation over the NiCo–S@CN/solar light system was as follows: pH 7.0 > pH 11.0 > pH 9.0 > pH 5.0 > pH 3.0. Moreover, NiCo–S@CN exhibited high TC degradation efficiency in multiple cycles while it remained chemically stable with undetectable soluble metals in the treated water. Results of electron spin resonance (EPR) and radical trapping studies indicated that holes (h + ) and superoxide radicals (O2 ˙ − ) were the main reactive species for efficient TC removal in the Z-scheme/solar light system. Overall, results demonstrated that NiCo–S@CN was a novel Z-scheme photocatalyst for the remediation of pharmaceutical-contaminated water.